Implementación de cuatro Métodos de Ensayo ASTM en la matriz crudo de petróleo basada en la Norma NTP ISO/IEC 17025 - Hernández Flores, Carla Lisseth (2021)
T The objective of this research work was to elaborate a plan of implementation of four ASTM methods in the crude oil matrix, adapting them to meet the requirements of the NTP ISO / IEC 17025 standard obtaining reliable test results. To achieve this, an initial assessment of compliance with the requirements of the Standard about to ASTM methods was first performed. Once this was specified, an implementation plan was drawn up. A sample of local crude oil was used to carry out the tests, following the steps indicated by each of the four ASTM methods, the results of the tests obtained did not show significant differences between their averages. The four test methods were validated, generating procedures, assurance programs and associated formats, and the uncertainty associated with each method was identified. Finally, the test results obtained were used to characterize the raw material as an intermediate crude according to the API density classification and as a sweet crude according to the sulfur content classification. Another characteristic of the local crude oil was its low water and sediment content and low salt content.